Training on Management Control System in Printing Entrepreneurs - Abd Karim, Mohd Rahimie bin; Lada, Suddin; Halim, Hendra; Kesuma, T. Meldi; Siregar, M. Ridha; Riyaldi, Muhammad Haris; Nizam, Ahmad; Majid, M Shabri Abd; Dawood, Taufiq Carnegie; Priantana, Riha Dedi; Sakir, A; Sari, Meutia Dwi Novita; Amir, Fakhrurrazi (Universitas Syiah Kuala, 2024)
This community service activity aimed to improve the management control systems of print entrepreneurs around Universitas Syiah Kuala (USK). The main issue was the lack of understanding and implementation of effective control systems, leading to operational inefficiencies. Using a Service Learning approach, 10 entrepreneurs participated in training led by experts from Universiti Malaysia Sabah (UMS) and USK. The training covered management control concepts and introduced basic technology tools to support business operations. Results showed a 25% increase in participants' understanding of management control systems and an 85% adoption rate of the techniques and technologies introduced. These improvements contributed to better business efficiency and align with Sustainable Development Goal 8, which emphasizes decent work and economic growth. This activity demonstrated that tailored training programs can significantly enhance small business operations and can be replicated for broader impact.